The Implementation Of Flexibility Enablers In Refurbishment Construction Project Management - Mubarok, Ristyawan Fauzi; Arviansyah (Jurnal Manajemen Bisnis, 2024)
This paper investigates the implementation of flexibility enablers in managing project to overcome project complexity or uncertainty. This research is using Q Methodology and in-depth interview with project management experts to understand practitioners’ perspective on flexibility and the implementation in project management practice. This research finds that there are 4 different perspectives on flexibility among refurbishment construction project practitioners and rank of flexibility enablers from the most important to the least important. It is shows that the top ranked flexibility enablers are always applied in construction projects in Indonesia except one flexibility enabler.